Contract agreement model for murabahah financing in Indonesia Islamic banking - Wulandari, Permata; , Niken Iwani Surya Putri; Kassim, Salina; Sulung, Liyu Adikasari (Emerald Group Publishing Limited, 2016)
The purpose of this paper is to measure the pattern of contract agreement process to map various banks’ position in perceiving Sharia conduct. This is done by incorporating the dynamics of culture, market demand and Sharia literacy in different banks. Finding of this research will serve as the formula to map the latent degree of Islamic bank’s commitment to their strategic vision and identity as an Islamic-based financial institution. This research develops its theoretical background in classical and contemporary literature review on murabahah contract in Islamic perspective. Focus group discussion (FGD) and in-depth interview are conducted on 32 bankers (in 14 Islamic banks), two National Sharia Council, five academicians and three central bank representatives as an input for qualitative analysis. Content analysis is utilized in this paper to emphasize the process of discovering the relationship between dynamic factors affecting contract agreement process in murabahah scheme in Indonesian banking. There are four dimensions affecting the contract agreement: fairness to customer,country regulation, perceived business practicality and product characteristic. The four dimensions are assumed to be influenced with categories proposed, as the category item is mostly repeated and is perceived to be significant in the participant’s perspective.